Selection of Rhizobium leguminosarum strains via symbiotic and production variables in Pisum sativum L. = Selección de cepas de Rhizobium leguminosarum por variables simbióticas y productivas en Pisum sativum L. - Piccinetti, Carlos Fabian; Eöry, Carolina Alba; Prieto, Gabriel Maria; Vallejo, Daniela Adriana; Enrico, Juan Martin; Salvagiotti, Fernando; Perticari, Alejandro (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2025)
Field pea (Pisum sativum L.) is a winter symbiotic legume that associates with Rhizobium leguminosarum sv viciae. This work aimed to evaluate strains of R. leguminosarum for their infective ability and early-plant growth, BNF contribution, biomass and grain yield. Seventy-eight specific strains and four pea cultivars were evaluated in a growth chamber, five strains and three cultivars were evaluated in a greenhouse, and three strains and two cultivars were evaluated in a field experiment. Only 44-55% of all evaluated strains were infective in the four cultivars. In the greenhouse, D70 and D156 strains showed the best nodulation variables as well as higher N content and yield. The field experiment showed D156 and D70 yielded a similar behavior for N content in canopy biomass and individual nodule biomass, whereas D191 had a higher nodule number per plant, aerial biomass and grain yields. D70 provided good nodulation, N content in biomass, and yield in the growth chamber, greenhouse, and field experiments, whereas D156 had a like or superior behavior in the greenhouse and field experiments. Therefore, D156 could constitute a good candidate for bacterial single-strain inoculants, as well as for formulating microbial consortia.